2018
DOI: 10.1158/1535-7163.mct-17-0965
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Potency and Impact of Carbon Ion Therapy in a Primary Mouse Model of Soft Tissue Sarcoma

Abstract: Carbon ion therapy (CIT) offers several potential advantages for treating cancers compared with X-ray and proton radiotherapy, including increased biological efficacy and more conformal dosimetry. However, CIT potency has not been characterized in primary tumor animal models. Here, we calculate the relative biological effectiveness (RBE) of carbon ions compared with X-rays in an autochthonous mouse model of soft tissue sarcoma. We used Cre/loxP technology to generate primary sarcomas in mice. Primary tumors we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 47 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…This is the first comprehensive study comparing CIRT and photon RT in combination with immune checkpoint inhibitors. However, the authors used the same physical dose of carbon ions and X-rays, despite the fact that RBE values of 1.5–2 based on clonogenic assay and an RBE of 3 based on growth delay assay for this cancer cell line have been reported, which makes the interpretation of the data biased [ 247 ]. To date, results on the efficacy of protons in combination with IO have not been reported.…”
Section: Charged Particle Radiation In Combination With Immunothermentioning
confidence: 99%
“…This is the first comprehensive study comparing CIRT and photon RT in combination with immune checkpoint inhibitors. However, the authors used the same physical dose of carbon ions and X-rays, despite the fact that RBE values of 1.5–2 based on clonogenic assay and an RBE of 3 based on growth delay assay for this cancer cell line have been reported, which makes the interpretation of the data biased [ 247 ]. To date, results on the efficacy of protons in combination with IO have not been reported.…”
Section: Charged Particle Radiation In Combination With Immunothermentioning
confidence: 99%
“…One may suspect about a more efficient activation of the cGAS/STING pathway or an enhanced release of DAMPs ( 74 , 75 ). Considering the temporal pattern of the immune response, the time scales between irradiation and radiation effects are expected to be modified after high LET radiation, accounting for the more severe inflicted damage ( 76 , 77 ). A faster manifestation of cell inactivation as compared to low-LET radiation suggests a more rapid immune activation and T cell recruitment, while at the same time providing a stronger delay in tumor growth.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Sørensen [24] compare tumor control, acute skin reactions and late radiation induced fibrosis in a mouse model. Brownstein et al [25] analyze the response of primary sarcomas in a mouse model after carbon ion irradiation. Systematic studies using different sublines of a syngeneic prostate carcinoma model have been reported in [26] [27][28] [29].…”
Section: In-vivo Studies Of Rbementioning
confidence: 99%